Efeitos do tipo de item e do monitoramento da fonte na criação e persistência de falsas memórias - Alves, Cintia Marques (2006)
False memories (FM´s) occur when we remember the events that never happened in reality, situations at which we were not present, and places where we never been to or when we remember some event differently from what really happened. The main purpose of this work was to check the durability of individual s memory after a time span of one week and to check the influence of the source monitoring on the creation of FM´s. For this, it was used the Deese-Roediger-McDermott (DRM) paradigm, which consists of the presentation of twelve lists of fifteen associated words (targets) to an undisclosed one which is called the critical distractor or critical nonpresented word. The individuals were picked among 80 UFU Psychology undergraduates who volunteer to participate. They were divided in two groups: auditory and visual ones. This separation was due to the difference in the modality of lists presentation at study. All participants were asked to pay attention to the words and half of them were asked to do the source monitoring of the words, whether it is auditory or visually form. Following the presentation of the twelve lists, they solved simple arithmetic problems. At last, it was done an immediate recognition memory test which has seventy words: thirty six studied itens (targets), twelve related lures (critical distractors) and twenty two unrelated lures (new words which were not semantically associated to any of the ten lists previously presented to them). One week later, they came back to do the delayed recognition memory test. The test and the procedure were the same as for the immediate recognition memory test. In these recognition tests they had to choose between Yes or No for each word, whether they did or did not recognize the words from one of the lists and they were asked to identify the word s source: Auditory or Visually form. The results showed that false memories are created and can be kept until one week later, more than real memories. Visual modality was better to the correct recognition (targets) and further more, it was responsible for the smaller rate of false recognition. Instructions to the individuals improved the source monitoring for targets, but it did not cut down on the misattribution for the critical distractor.